FACTORS EXPLAINING THE PRODUCT INNOVATION OF ENTREPRENEURIAL STUDENT: A THEORETICAL APPROACH - Wafa, Harfianti Nur; Suparno; Lutfia, Annisa (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
Entrepreneurship education emphasizes learning through business practices with student competencies capable of innovation. This research aims to develop theoretical modeling of the product innovation process for students in entrepreneurship programs in higher education. The theory used in this research is product innovation in both entrepreneurship development and education. Various factors influence product innovation for students as SMEs, analyzed and identified as the main factors in product innovation for entrepreneurial students, namely entrepreneurship education and creativity. The research method used is qualitative with literature study, theoretically analyzing previous theories and researchers and determining the main factors as predictors of the formation of educational product innovation. Grounded theory, with comparison of various correlation results as the findings of this research. Shows that creativity is a mediator of entrepreneurship education towards product innovation. Recommendations for future researchers to be able to examine the influence of entrepreneurship education on student product innovation with creativity as mediation, whether tested quantitatively, or developed on other broader aspects of variables. Keyword: entrepreneurship education; student creativity; product innovation; higher education.